Nota preliminar trabalhos arqueológicos no sítio do Paleolítico Médio da Conceição - Raposo, Luís (2017)
Preliminary notes on archaeological work done at Sítio da Conceição (Alcochete) following the beginning of road works for the access to the Tagus bridge under construction. The lithic industry collected points to a highly interesting cultural framework of the Late Middle Paleolithic, which should be related to contemporary settlements on the Setúbal and Lisbon peninsulas,